PENERAPAN PELAYANAN PRIMA OLEH JURU PELIHARA CANDI MUARA TAKUS KABUPATEN KAMPAR PROVINSI RIAU - ", Zulfahmi; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research entitled Application of Excellent Service by the Caretaker of Muara Takus Temple, Kampar Regency, Riau Province. This study aims: (1) to find out how the implementation of excellent service by the caretakers of Muara Takus Temple, Kampar Regency has been implemented in accordance with the A4 concept of excellent service, (2) to find out the obstacles in implementing excellent service at Muara Takus Temple, Kampar Regency. The sample used in this study was 100 people, the sampling technique was determined using accidental sampling techniques, this study used a mixed method to determine the problems raised in this study. This research was conducted at Muara Takus XIII Koto Kampar Temple, Muara Takus Village, Kampar Regency, Riau Province. The research was conducted for 4 months, starting from January 2021 – April 2021. The data collection techniques used observation, questionnaires, interviews and documentation. The samples of this research are visitors who have visited Muara Takus Temple, Kampar Regency. The results of this study indicate that overall the respondents gave good responses to the application of excellent service to the caretakers of Muara Takua Temple, Kampar Regency, this is evidenced by the results of the scores from the responses of visitors who have visited Muara Takus Temple, Kampar Regency with good scores. Excellent service is the most important value for a tourist attraction engaged in services. Keywords: Excellent Service, Caretaker, Muara Takus Temple